Asbabun Nuzul Ayat 174 Surah Al-Baqarah dan Hubungannya dengan Allah Pencipta Langit dan Bumi (Pusat Riset dan Inovasi Nasional, 2024)
This research examines the Asbābun Nuzūl of verse 174 of Surah Al-Baqarah and its relationship with faith in Allah as the Creator of the heavens and the earth. This verse contains a strong warning against those who conceal Allah’s revelations and exchange divine truth for worldly gain. Using a qualitative approach based on library research, this study analyzes the historical background of the revelation, its socio-religious context, and interpretations from classical and contemporary Qur’anic scholars. The findings indicate that the Asbābun Nuzūl of verse 174 is closely related to the behavior of certain People of the Book who deliberately hid the truth about the prophethood of Muhammad ﷺ for personal interests. Such actions reflect a weak acknowledgment of Allah’s absolute authority as the Creator and Sustainer of the universe. The connection between this verse and Allah as the Creator of the heavens and the earth emphasizes that all knowledge, revelation, and truth originate solely from Him and must not be manipulated for material benefit. This research is expected to strengthen Islamic theological understanding regarding the obligation to convey truth honestly and to reinforce faith in Allah as the ultimate source of creation, guidance, and moral responsibility.